The Effect of Leadership Style and Motivation on Employee Performance - Arisman (Jurnal Multidisiplin Madani, 2022)
The leadership style in today's development is certainly very necessary, because the leadership style must be able to adapt it, in this article it consists of leadership style variables, motivation and employee performance, using a literature review methodology of about 75 articles, in this case it is found that leadership style has a significant relationship with employee performance, a leader influences employees in carrying out their leadership responsibilities. Communication skills are one of the most important leadership style competencies. Lack of motivation has a negative effect on employee performance. Employee motivation is a problem that many organizations face. Leadership style in communicating with employees affects employee performance. Therefore, researchers should explore the relationship of leadership styles that can be used to increase motivation on employee performance, leadership style and motivation require a better understanding of the strategies needed to improve the performance of their employees.